Effectiveness and Safety Studies of Omalizumab in Children and Adolescents With Moderate-To-Severe Asthma. (April 2023) - Cheng, Lu; Yang, Tianrui; Ma, Xiang; Han, Yuling; Wang, Yongtai
Background: Omalizumab is currently approved for the treatment of moderate-to-severe allergic asthma in patients 6 years and older.Objective: To assess the effectiveness and safety of subcutaneous omalizumab as an add-on therapy option for moderate–severe allergic asthma in patients aged 6—20 years old.Methods: The studies published from July, 1970 to May, 2021 were searched from the electronic databases which followed keywords: ("anti-IgE" OR "anti-immunoglobulin E" OR "anti-IgE antibody" OR "omalizumab" OR "rhuMAb-E25" OR "Xolair") AND "asthma" AND ("child" OR "children" OR "adolescents" OR "youth" OR "teenager" OR "kids" OR "pediatric"). Thirteen studies were pooled to determine the effectiveness and safety of omalizumab. Efficacy endpoints were evaluated using a fixed-effects model or a random-effects model depending on heterogeneity. Safety endpoints were evaluated by odds ratio.Results: Thirteen studies were included. In this meta-analysis, our results showed that fractional exhaled nitric oxide and asthma control test scores were significantly improved with omalizumab treatment. Serum immunoglobulin E was also decreased in children with moderate-to-severe asthma after treatment with omalizumab. The analysis found that there was no significant difference between pre-and post-treatment in forced expiratory volume in one second/ forced vital capacity ratio, forced expiratory flow between 25 and 75% of vital capacity, or FEV1. Overall, more adverse events occurred with omalizumab compared to placebo. However, the degree was mild to moderate.Conclusion: This meta-analysis indicates that omalizumab is safe and effective to treat children and adolescents with moderate-to-severe asthma.